Structural determinants of ligand binding in truncated hemoglobins: Resonance Raman spectroscopy of the native states and their carbon monoxide and hydroxide complexes. Issue 10 (30th March 2018) - Feis, Alessandro; Howes, Barry D.; Milazzo, Lisa; Coppola, Daniela; Smulevich, Giulietta
Abstract: The ligand binding characteristics of heme‐containing proteins are determined by a number of factors, including the nature and conformation of the distal residues and their capability to stabilize the heme‐bound ligand via hydrogen‐bonding and electrostatic interactions. In this regard, the heme pockets of truncated hemoglobins (TrHbs) constitute an interesting case study as they share many common features, including a number of polar cavity residues. In this review, we will focus on three proteins of group II TrHbs, from Thermobifida fusca ( Tf ‐HbO) and Pseudoalteromonas haloplanktis TAC125 ( Ph ‐HbO). Although the residues in positions G8 (Trp) and B10 (Tyr) are conserved in all three proteins, the CD1 residue is a Tyr in T. fusca and a His in P. haloplanktis . Comparison of the ligand binding characteristics of these proteins, in particular the hydroxo and CO ligands by means of resonance Raman spectroscopy, reveals that this single difference in the key heme cavity residues markedly affects their ligand binding capability and conformation. Furthermore, although the two Ph ‐HbOs ( Ph ‐HbO‐2217 and Ph ‐HbO‐0030) have identical key cavity residues, they display distinct ligand binding properties. Abstract :